2000
DOI: 10.2136/sssaj2000.641275x
|View full text |Cite
|
Sign up to set email alerts
|

Using Paper De‐inking Sludge to Maintain Soil Structural Form Field Measurements

Abstract: A high level of organic matter in soils is crucial to maintain structural stability but organic matter sources differ in their effectiveness in stabilizing structural units. Objectives of this study were, first, to determine the optimal rate of sludge and fertilizer application to improve soil physical properties, and second, to investigate a possible correlation between hydraulic conductivity and structural stability measurements. A 4‐yr field study (1994–1997) was conducted on three different soil types to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 33 publications
5
20
0
1
Order By: Relevance
“…However, an increase in soil water content in DSPC-treated plots was not observed in 1997, suggesting that the presence of undecomposed material in the DSPC was responsible for this temporary increase. Similar shortterm effects were reported previously for raw de-inking paper sludges (Trépanier et al 1996;Aitken et al 1998;Simard et al 1998a), combined primary and secondary sludges (Cambouris et al 2000;Nemati et al 2000) and manure and commercial composts (Gagnon et al 1998). For personal use only.…”
Section: Soil Water Content and Phsupporting
confidence: 83%
“…However, an increase in soil water content in DSPC-treated plots was not observed in 1997, suggesting that the presence of undecomposed material in the DSPC was responsible for this temporary increase. Similar shortterm effects were reported previously for raw de-inking paper sludges (Trépanier et al 1996;Aitken et al 1998;Simard et al 1998a), combined primary and secondary sludges (Cambouris et al 2000;Nemati et al 2000) and manure and commercial composts (Gagnon et al 1998). For personal use only.…”
Section: Soil Water Content and Phsupporting
confidence: 83%
“…Similarly, Kaddous andMorgans (1986), andMurphy (2001) reported an increase ( p < 0Á05) in percent water-stable aggregates as a result of SMC application. Amendments of either type of SMC had the capacity to increase the aggregate stability of the soil it was applied to, however, and similar to the observations reported by Nemati et al (2000) and Gagnon et al (2001) for paper residue amendments, neither fresh nor composted SMC amendment universally enhanced soil structural stability. Despite this, it was observed that fresh SMC amendments on occasion yielded more resistance aggregates than did similar additions of composted SMC.…”
Section: Aggregation Induced By Fresh and Composted Smcsupporting
confidence: 77%
“…The abundance of aggregates >5 mm and the mean weight diameter of aggregates were reported to decrease when the fresh combined paper sludge was added to soil with mineral N fertilizer (Bipfubusa et al 2005), also implying that benefits to aggregation are dependent on relatively undecomposed sludge. Lower sludge rates resulting in lesser increases in soil organic matter in the studies of Trépanier et al (1996a) and Nemati et al (2000) may explain the less persistent effects on soil aggregation in comparison with the research of Chantigny et al (1999) and Gagnon et al (2001). Zibilske et al (2000) clearly showed that the onset and magnitude of decreased bulk density and increased aggregation of a fine sandy loam were dependent on the rate (45 to 235 Mg ha -1 ) and frequency (once, biennially, and annually) of combined sludge application.…”
Section: Soil Bulk Density and Aggregationmentioning
confidence: 69%
“…Wet aggregate stability of a silty clay and a loamy soil was increased 15-17% by application of a combined sludge (C:N ratio of 160:1, 85% deinking sludge/15% secondary sludge) at 8 to 24 Mg ha -1 (Nemati et al 2000). Enhanced stability persisted for about 1 yr, indicating annual applications were necessary for continuous benefit.…”
Section: Soil Bulk Density and Aggregationmentioning
confidence: 99%